Kazakhstan: Optimization of state management of investments in agriculture - Shaldarov, Baltabek; Oralbayeva, Zhanar; Syzdykov, Beibit; Medeni, Тunс; Omirtay, Amalbek (International Journal of Innovative Research and Scientific Studies, 2025)
In the context of increasing global competition, climate challenges, and the need for food security, improving mechanisms for state regulation of investment activities in the agricultural sector is of particular importance. This study aims to develop an optimization model for managing agricultural investments in the Republic of Kazakhstan. The work contains a systematic analysis of existing support instruments, identifies key institutional and infrastructural barriers, and studies international experience. A five-level adaptive model is proposed, including strategy, normative, economic, institutional, and information-analytical subsystems. KPI/KQI indicators have been developed to assess efficiency, and a logical matrix (logFrame) with elements of scenario modeling has been introduced. A conclusion has been reached about the need to move from fragmented subsidies to a flexible, digital, and results-oriented system of state stimulation of agricultural investments. The presented model can serve as a tool for transforming investment policy and increasing the sustainability of the agricultural sector.